PENGARUH METODE KOLABORATIF TERHADAP HASIL BELAJAR MEMBILANG SAMPAI DENGAN 100 KELAS II SEKOLAH DASAR - Nabila Devi Aprilillah; Nurhayati, Eni; Ludfy Hadis Maqfiro, Mochammad (Pedagogik : Jurnal Pendidikan Guru Sekolah Dasar, 2025)
The process of learning mathematics in second-grade elementary school often lacks engagement and tends to make students passive, particularly in counting materials up to 100. This study aims to investigate the extent to which the collaborative learning method influences the counting skills of second-grade students. The research employed a quantitative approach using a quasi-experimental design, involving 38 students divided into an experimental group and a control group. Data collection techniques included tests (pretest and posttest), observations, and questionnaires. The results revealed that the average posttest score of the experimental group (84.76) was higher than that of the control group (75.41), as indicated by a significance value of 0.028, which is less than 0.05. The calculated N-Gain score of 0.42 falls within the medium category, while the questionnaire results showed that student responses were in the ‘very good’ category with an average score of 89.52. Based on these findings, it can be concluded that the collaborative learning method is effective in improving students' counting skills, while also enhancing their engagement and motivation in learning mathematics at the lower elementary level.